The double tax consequence of the new double tax treaty between South Africa and Mauritius for persons other than individuals - Broun, Stanley (Department of Finance and Tax, 2016)
Mauritius continues to be among the most competitive, stable, and successful economies in Africa. Mauritius actively seeks foreign investment and prides itself on being open to foreign investment. Mauritius amongst other countries is one of the recipients of high volume foreign direct investment (FDI) and is well known for its favourable tax regime. This favourable tax regime remains one of the key reasons why South Africans use Mauritius as a preferred jurisdiction, well suited for passive investments as well as being an investment hub to establish and grow their foreign business activities. In 1996 SA concluded a double tax treaty ('DTT') with Mauritius to guard against potential double taxation. This could occur when a person is considered a tax resident in both South Africa and Mauritius by virtue of the application of the respective tax laws of these countries. The application of the DTT will however result in such a person being deemed to be resident in only one of the countries party to the DTT. On the 17 March 2013 SA signed a new DTT with Mauritius, which will bring about some significant changes for South Africans who have FDI in Mauritius. Of significance are the amendments to Article 4 in the DTT. The new tiebreaker rule provides that the Competent Authorities of the two Contracting States will by mutual agreement endeavour to decide which country has taxing rights in the case of persons other than individuals. This significant change has multiple effects on persons other than individuals and this can lead to a person in fact becoming subject to double taxation. This paper will investigate the effect of the change between Article 4 in the DTT concluded in1996 (in force from 20 June 1997) and the new Article 4 in the DTT signed on the 17 May2013 which came into effect from the 1 January 2016 for South Africans who have foreign direct investments in Mauritius. In conclusion the principles outlined in the relevant chapters will be presented through a practical application of determining if a person other than an individual is subject to double taxation. The application of the domestic laws of both SA and Mauritius and the application of the New IN6 will be applied to an offshore trust established in Mauritius. With the application of the principles and procedures one will be able to see the effect of the tie-breaker rule in the new DTT concluded on the 17 March 2013 between SA and Mauritius.